Effects of different orchard tree pruning residues on the yield and nutrient composition of Lentinus edodes - Zhang, Yuanyuan; Li, Quanshun; Duan, Longfei; Ding, Jian; Li, Yue; Wang, Yong; Xu, Hongyan; Qin, Baofu (Frontiers in Nutrition, 2024)
As the scale of Lentinus edodes cultivation expands, issues such as substrate shortages and rising production costs have become increasingly prominent in mushroom forest. To evaluate the feasibility of fruit tree pruning residue as a substrate in cultivating L. edodes, we analyzed the effects of different ratios of Quercus sawdust (QS), Malus pumila pruning (MPP), Vitis vinifera pruning (VVP), Actinidia deliciosa pruning (ADP), Ziziphus jujuba pruning (ZJP), and Morus alba pruning (MAP) on the yield, amino acid, and protein content in the fruit bodies of L. edodes. The yield from the QS-MPP, QS-VVP, QS-ZJP, and QS-MAP groups increased by 14.86%, 8.1%, 18.92%, and 22.97%, respectively, compared with that of the control (80% QS). The ash content in the MAP group increased by 21.21% compared with that of the control. The highest crude protein content was found in the QS-MAP group, increasing by 10.84% that of the control. The QS-MPP group showed the highest crude fiber content at 1.72 g/100 g. The crude polysaccharide and crude fat contents in the ZJP group increased by 110.77% and 10.15% those of the control, respectively. The QS-MPP group exhibited the highest contents of calcium, potassium, manganese, and magnesium, showing increases of 60.26%, 31.36%, 29.94%, and 34.43% those of the control, respectively. VVP had the highest contents of iron and copper, with increases of 179.09% and 65.27% compared to those of the control, respectively. QS-VVP had the highest zinc content while QS-ZJP had the highest selenium content. MPP had the highest sodium content with an increase of 68.02% from that of the control. The QS-MPP group exhibited the highest levels of threonine, valine, isoleucine, serine, cysteine, glycine, and histidine, whereas the QS-VVP treatment resulted in the highest levels of leucine, aspartate, glutamate, and arginine, showing increases of 6.34%, 6.09%, 9.51%, and 8.7%, respectively, over the control. The best formulation was determined to be 40% QS, 40% MPP, 17% bran, 1% sucrose, 1% CaCO3, and 1% gypsum. Collectively, these results demonstrate that fruit tree pruning residue as a substrate can support sustainable L. edodes cultivation while maintaining high yield and nutritional quality.